Scrotal Abscess as Initial Presentation of Squamous Cell Carcinoma - Kathy H. Huen; Paymon Nourparvar; John J. DeCaro; Mark D. Walsh; Muta M. Issa; Chad W. M. Ritenour (Case Reports in Urology)
We report a case of scrotal squamous cell carcinoma in a 67-year-old man that presented as a recurrent nonhealing scrotal abscess. Radical scrotectomy and bilateral simple orchiectomy were performed. A pudendal thigh flap was used for wound closure. To our knowledge, this is the first report of its use after radical surgery for scrotal cancer. The clinical features, staging, and treatment of scrotal squamous cell carcinoma are reviewed. In this report, we highlight the importance of including scrotal cancer in the differential diagnosis when evaluating a scrotal abscess.